2020
DOI: 10.2174/1574884714666190823162055
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Perception of Thromboembolism and Thromboprophylaxis among Hospitalized Patients in Jordan

Abstract: Background and Objective: Despite the established importance of thromboprophylaxis in patients with Venous Thromboembolism (VTE), a limited number of studies have assessed the awareness of VTE and thromboprophylaxis therapy among the affected patients. The aim of the current study was to assess awareness and to explore variables associated with awareness about VTE and its thromboprophylaxis. Methods: A cross-sectional study was conducted on hospitalized patients who received thromboprophylaxis (5000 units of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 13 publications
8
7
0
Order By: Relevance
“…This finding shed light on the vital role of health-care providers in educating their patients about the benefits of ambulating during hospitalization. This finding is in agreement with other studies that were conducted in Jordan, 10 Saudi Arabia, 14,21 and Canada. 13 Another study that was conducted to measure global public awareness of nine countries, including the United States, the United Kingdom, the Netherlands, Thailand, Japan, Germany, Canada, Australia, and Argentina, showed that immobility is the most recognized VTE risk factor in these countries.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…This finding shed light on the vital role of health-care providers in educating their patients about the benefits of ambulating during hospitalization. This finding is in agreement with other studies that were conducted in Jordan, 10 Saudi Arabia, 14,21 and Canada. 13 Another study that was conducted to measure global public awareness of nine countries, including the United States, the United Kingdom, the Netherlands, Thailand, Japan, Germany, Canada, Australia, and Argentina, showed that immobility is the most recognized VTE risk factor in these countries.…”
Section: Discussionsupporting
confidence: 94%
“…This result could be attributed to the fact that Yemeni patients were unaware that PE is considered a complication of DVT. This finding agrees with the study conducted in Jordan by Jarab et al 10 On the other hand in developed countries, a study from Canada by Saga et al found that most hospitalized patients (81.2%) had good knowledge of both DVT and PE. 13 Another study from the United States by Konieczyńska et al reported that younger patients had good knowledge about VTE in general.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations